Functional Traits of Stem and Leaf of Wrightia candollei S. Vidal.
Morpho-anatomical functional traits of native tree species are deemed important in forest restoration. Although much is known about morpho-anatomical traits of many terrestrial plants, such traits in Philippine native trees remain unclear. In this study, the stem and leaf morpho-anatomy of W. candollei S. Vidal was investigated to provide insights on its potential for restoration of dry, degraded lands. Results suggest that the morpho-anatomical structure of leaf and stem of W. candollei conforms to characteristics typical of plants adapted to dry areas and to species commonly used for restoration. The presence of trichomes, multiple layers of storage cells and mechanical cells, sclerenchymatic phloem cap, multiple vascular bundles, living xylem parenchyma, and steep leaf inclination were observed and interpreted as important leaf and stem structural traits of W. candollei. These morpho-anatomical traits are commonly associated with (1) solar radiation and water loss reduction; (2) tissue/organ mechanical reinforcement; and (3) water uptake and storage. Therefore, W. candollei ? in association with the other native species ? might be potentially useful for restoration of dry degraded lands in the Philippines. However, ecophysiological and phenological studies, as well as watering regime experiments, are recommended to better understand the actual habitat preference of the species.